Multivariable adaptive algorithms for reconfigurable flight control - Bodson, M.; Groszkiewicz, J.E. (IEEE transactions on control systems technology, 1997)
The application of multivariable adaptive control techniques to flight control reconfiguration is considered. The objective is to redesign automatically flight control laws to compensate for actuator failures or surface damage. Three adaptive algorithms for multivariable model reference control are compared. The availability of state measurements in this application leads to relatively simple algorithms. The respective advantages and disadvantages of the adaptive algorithms are discussed, considering their complexity and the assumptions that they require. An equation-error based algorithm is found to be preferable. Simulations obtained using a full nonlinear model of a twin-engine jet aircraft are presented. The results demonstrate the ability of the adaptive algorithms to maintain trim after a failure, to restore tracking of the pilot commands despite the loss of actuator effectiveness, and to coordinate the use of the remaining active control surfaces in order to guarantee the decoupling of the rotational axes. A new adaptive algorithm with a variable forgetting feature is also used and is found to yield a useful alternative to covariance resetting as a solution to covariance wind-up in least-squares algorithms.